2022
DOI: 10.3389/fimmu.2022.957224
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 modulates virus receptor expression in placenta and can induce trophoblast fusion, inflammation and endothelial permeability

Abstract: SARS-CoV-2 is a devastating virus that induces a range of immunopathological mechanisms including cytokine storm, apoptosis, inflammation and complement and coagulation pathway hyperactivation. However, how the infection impacts pregnant mothers is still being worked out due to evidence of vertical transmission of the SARS-CoV-2, and higher incidence of pre-eclampsia, preterm birth, caesarian section, and fetal mortality. In this study, we assessed the levels of the three main receptors of SARS-CoV-2 (ACE2, TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Other studies also showed an increase in COVID-19-infected placental apoptosis, although indirectly, including an increase of proapoptotic Bax protein 27 and Caspase 3/7 induction in the infected placental cell line. 23 In particular, interferon-γ, which was elevated in this study, is known to induce trophoblast apoptosis, 28 which also occurs in other clinical circumstances, including preeclampsia and toxoplasma infection. 25 29 …”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Other studies also showed an increase in COVID-19-infected placental apoptosis, although indirectly, including an increase of proapoptotic Bax protein 27 and Caspase 3/7 induction in the infected placental cell line. 23 In particular, interferon-γ, which was elevated in this study, is known to induce trophoblast apoptosis, 28 which also occurs in other clinical circumstances, including preeclampsia and toxoplasma infection. 25 29 …”
Section: Discussionmentioning
confidence: 65%
“… 20 21 22 Our observation revealed that the trophoblast villous cells expressed both ACE-2 and a significantly higher amount of TMPRSS2 in the COVID-19 group, which has also been reported in previous studies. 10 23 24 This protease increment showed facilitation and active priming in host cells, which will be an important factor in the entry of viral infections. 19 23 Lower levels of ACE2 protein in placentas from COVID-19-positive pregnancies have also been reported in a previous study, hinting that SARS-CoV-2 infection and inflammation may directly or indirectly downregulate ACE2 expression as a result of active shedding.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Numerous studies suggest that ACE-2 and TMPRSS2 expression is negligible in first, second, and third trimester placental cells ( Gengler et al, 2021 , Pique-Regi et al, 2020 ). However, SARS-CoV-2 infection may be associated with vascular injury in pregnant women, in whom ischemic damage to the placenta may facilitate viral cell entry ( Agostinis et al, 2022 , Edlow et al, 2020 ). There may also be other cellular mediators that may be responsible for cell entry such as cathepsin L, FURIN, and sialic acid-binding Ig-like lectin 1 ( Pique-Regi et al, 2020 ).…”
Section: Obstetrical Complications and Impact On The Fetus/newbornmentioning
confidence: 99%